Genetic Diversity and Population Structure of Alpacas (Vicugna pacos) in Peru: A Microsatellite Analysis - Wilber Peralta; Agustin Nestares; Julyssa Gamarra; Miler Rojas; Juan Sullca; Richard Estrada (Diversity)
This study evaluated the genetic diversity and population structure of Vicugna pacos (Huacaya alpacas) from two contrasting breeding contexts in Junín, Peru: the genetically managed herd of INIA’s Santa Ana Experimental Station (Suitucancha) and the community-based herd of Huayre, where natural, unregulated mating practices are common. An external reference population from Quimsachata was also included. Genetic diversity parameters revealed high allelic richness and heterozygosity within all populations. Analyses of molecular variance (AMOVA), principal coordinate analysis (PCoA), Bayesian clustering, and phylogenetic reconstruction indicated moderate genetic differentiation between Suitucancha and Huayre, likely influenced by the use of selected males under controlled mating in Suitucancha versus natural, unregulated group mating in Huayre, which facilitates broader gene flow. The Quimsachata group displayed distinct genetic characteristics, likely reflecting limited gene flow due to its role as a germplasm conservation nucleus under closed reproductive management. These results reflect how differences in reproductive management may influence population structure in alpacas.